Measures of sky quality (seeing) using the DIMM technique at the Huancayo Observatory - Meza, Erick (2013)
We show the implementation of an instrument to measure the sky quality for astronomical purposes (seeing) using the Differential Image Motion Monitor technique. This instrument let us an acute and systematic measurement of seeing along with its temporal evolution. We monitored seeing at Huancayo Observatory during seven consecutive nights in 2012 August. Mean seeing was 1.34” ± 0.33”. In 14% of the observed time, seeing was below than 1”, and in 71% below than 1.5”. The successful implementation of this technique and its applicability let us using this instrument in several places where a program of site testing will be scheduled in Peru. The selection of a professional astronomical facility (as an astronomical observatory) will be benefited with DIMM measurements.